Cost-Benefit Analysis of Implementing a Paperless Accounting System Using the Evizia Application at JIH Yogyakarta - Irwan Fadli Jailani Hasibuan; Nurfauziah Nurfauziah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Digital transformation encourages healthcare institutions to adopt more efficient accounting systems, including paperless accounting. JIH Yogyakarta Hospital implemented the Evizia application to address inefficiencies caused by paper-based accounting processes. This study aims to analyze the benefits and compare the costs and benefits of implementing a paperless accounting system using Evizia with the conventional system. A descriptive qualitative method with a cost-benefit analysis (CBA) approach was employed through interviews, observations, and documentation. The results indicate that Evizia improves administrative efficiency, accelerates financial reporting, enhances data accuracy and internal control, and reduces paper usage by approximately 30%, despite additional costs related to system leasing and maintenance. Overall, the implementation of the Evizia paperless accounting system is considered feasible and provides long-term strategic benefits for operational efficiency, financial governance, and environmental sustainability at JIH Yogyakarta Hospital.